A global existence and uniqueness result for a stochastic Allen–Cahn equation with constraint. (29th March 2017) - Bauzet, C.; Bonetti, E.; Bonfanti, G.; Lebon, F.; Vallet, G.
Abstract : This paper addresses the analysis of a time noise‐driven Allen–Cahn equation modelling the evolution of damage in continuum media in the presence of stochastic dynamics. The nonlinear character of the equation is mainly due to a multivoque maximal monotone operator representing a constraint on the damage variable, which is forced to take physically admissible values. By a Yosida approximation and a time‐discretization procedure, we prove a result of global‐in‐time existence and uniqueness of the solution to the stochastic problem. Copyright © 2017 John Wiley & Sons, Ltd.